Dylematy związane z wprowadzaniem zmian w organizacji w kontekście wdrażania controllingu - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Dilemmas of introducing changes into organization in context of implementing the controlling, 2006)
A necessity of introducing changes in an organization in connection with implementing the controlling was justified. The stages of implementing the controlling and required to fulfilling in this context preliminary conditions were listed. That was the basis to presenting sorts of changes in an organization. Primary and secondary conditions of implementing the controlling, and connected with functioning as well, were discussed. The most basic dilemmas to solve in this frames were accentuated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 532-539